KIYAI AND BEJINGAN: LOCAL POLITICAL ELITE AND THE HEGEMONIC CULTURE - Moh. Syaeful Bahar (JICSA : Journal of Islamic Civilization in Southeast Asian, 2014)
this paper examines the issue of effective local leadership within santri in relation to the framework of building democratic governance at the local level in the community centre point. The author employs a qualitative research through case study. The main issue of this research is the political role of kiyai and bejingan in Bondowoso, East Java. This study indicate that the new trend, that is the socio-political power collaboration of the kiyais and the bejingans, does not have any positive implications for the development of democracy at the local level and for the critical awareness of society. In fact, with this trend, the hegemony and marginalization of the society’s political consciousness are relatively increasing. One of the major reasons is, that there are no longer two or more forces to control over each other.